Analisis Gempa Nonliear Pushover dengan Metode Apllied Technology Council (ATC-40): Studi Kasus: Bangunan Baja, Pabrik Santos Premium Krimer Tower Plant 3A, Sidoarjo - Klemens Raditya Maulana (Jurnal Kendali Teknik dan Sains, 2025)
. The phenomenon of a potential megathrust earthquake predicted to occur in the coming years has raised widespread concern among the Indonesian public, particularly due to the high vulnerability of existing structures. In response to this issue, this study aims to analyze the structural capacity of buildings in resisting seismic forces and lateral loads, with a specific focus on factory structures. As a civil engineering student specializing in structural engineering, the objective of this research is to examine the behavior, performance, and potential failure patterns of building structures under earthquake loads. The research method employs pushover analysis as a tool for structural assessment, while the evaluation process refers to the guidelines outlined in ATC-40. The analysis results indicate that the factory structure is capable of withstanding a lateral load of 108,587.40 kN, with a controlled roof displacement of 1.5 meters. The structural performance level is categorized under the Damage Control (DO) stage, specifically at performance level SP-2, where the structure remains standing under lateral loads but experiences damage requiring repair before reuse. Furthermore, the failure patterns observed reveal a progressive performance of structural elements, shifting from condition B (Basic), IO (Immediate Occupancy), LS (Life Safety), C (Collapse Prevention), up to E (Extreme Damage). These findings highlight the importance of proper structural design and evaluation in enhancing resilience, ensuring safety, and minimizing potential risks from future megathrust earthquake events.